1998
DOI: 10.1093/nar/26.16.3651
|View full text |Cite
|
Sign up to set email alerts
|

Telomere analysis by fluorescence in situ hybridization and flow cytometry

Abstract: Determination of telomere length is traditionally performed by Southern blotting and densitometry, giving a mean telomere restriction fragment (TRF) value for the total cell population studied. Fluorescence in situ hybridization (FISH) of telomere repeats has been used to calculate telomere length, a method called quantitative (Q)-FISH. We here present a quantitative flow cytometric approach, Q-FISHFCM, for evaluation of telomere length distribution in individual cells based on in situ hybridization using a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
211
1
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(224 citation statements)
references
References 26 publications
7
211
1
5
Order By: Relevance
“…We found that the telomere-specific fluorescence of mid-S and G 2 /M phase PBMC in each cell division generation was 150% 6 4% and 196% 6 3% (mean 6 SEM), respectively, of that in G 0 /G 1 phase PBMC (Fig. 3), similar to values previously reported for G 0 /G 1 , S, and G 2 /M phase cells in populations of proliferating lymphoid cells (9,16). We noted that although the substan- tial intercellular heterogeneity in telomere-specific fluorescence within each cell division generation would preclude assigning a single cell to a particular cell division generation based upon telomere signal (e.g., Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We found that the telomere-specific fluorescence of mid-S and G 2 /M phase PBMC in each cell division generation was 150% 6 4% and 196% 6 3% (mean 6 SEM), respectively, of that in G 0 /G 1 phase PBMC (Fig. 3), similar to values previously reported for G 0 /G 1 , S, and G 2 /M phase cells in populations of proliferating lymphoid cells (9,16). We noted that although the substan- tial intercellular heterogeneity in telomere-specific fluorescence within each cell division generation would preclude assigning a single cell to a particular cell division generation based upon telomere signal (e.g., Fig.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, shorter telomere length in blood cells has been associated with earlier mortality in older populations (8). Interest in quantitating telomere length prompted development of a sensitive assay for measuring telomere length, flow cytometric analysis of fluorescence in situ hybridization (flow-FISH) (9,10). In this method, the mean telomere length in individual cells is determined by quantifying the fluorescence emanating from fluorochromeconjugated peptide nucleic acid (PNA) probes hybridized to telomeric DNA repeat sequences (reviewed in (11)).…”
mentioning
confidence: 99%
“…To increase the accuracy of measurements, we tested the addition of control cells as an internal standard as was suggested by Hultdin et al (21) We chose diploid cow thymocytes as an internal control, which are abundantly available, have about two times longer telomeres than human cells and which proved to have very little variation in telomere length between cells. After mild fixation with 1% formaldehyde, such fixed cow thymocytes can be easily distinguished from unfixed, flow-FISH processed cells based on their weaker staining with the DNA dye LDS 751 as seen in Figure 2.…”
Section: Results and Discussion Automation And Internal Standardmentioning
confidence: 99%
“…We have chosen the median value as cutoff level, but the true border to divide the material into prognostic groups deserves further investigation. Recently described techniques for flow cytometric analysis after in situ hybridisation with a fluorochrome labelled telomere probe ('flow-FISH') can be useful (Rufer et al, 1998;Hultdin et al, 1998), since the flow-FISH approach is convenient and can be directly applied to material sent for regular diagnostic work. However, further studies of larger groups of patients have to be performed to clarify the clinical impact of telomere length analysis in CLL.…”
Section: Discussionmentioning
confidence: 99%